Targeted disruption of the Sty dual specificity kinase. - Ginsberg, Simon Dominic. (University of Ottawa (Canada), 1997)
Dual specificity kinases are known to have important roles in cellular regulation. The Sty dual specificity kinase has been shown to segregate with, and phosphorylate, SR family splicing factors, but the consequences of this are not known. Additionally, it is not known if the kinase has any other regulatory functions. In an attempt to determine the function of this protein in a mammalian system, Sty deficient mice were generated. This was accomplished through gene targeting, in ES cells, with a promoterless IRES-$\beta Geo$ based vector. Using this efficient system, we obtained an 82% recombinant frequency. This is in contrast to a PGK-neo based vector, targeting the same locus, for which none of 377 clones were homologous recombinants. The knockout mice generated exhibit no overt phenotype, though more detailed analysis is still in progress. A possible explanation for the lack of a phenotype is a potential redundancy between Sty and closely related family members, one of which has recently been identified.
Keywords: Biology, Molecular.